Microstructural characteristics and mechanical properties of Sn-Ag-Cu solders with minor additions of Al and Zn / Leong Yee Mei - Leong , Yee Mei (2020)
Driven by the recent trend towards miniaturization of lead free electronic products, researchers are putting immense efforts to improve the properties and reliability of Sn based solders. Recently, much interest has been shown on low silver (Ag) content solder SAC 105 (Sn-1.0Ag-0.5Cu) solder because of economic reasons and improvement of impact resistance as compared to SAC387(Sn-3.8Ag-0.7Ag). The present work investigates the effect of minor (0.1-0.5wt.%) Aluminium (Al) and Zinc (Zn) addition to SAC105 on the bulk and interfacial structure between solder and copper substrate during reflow and after thermal aging , the mechanical properties of the solder joint and the nano-mechanical properties of IMC formed. Al and Zn have been chosen as they have shown promising results in improving the solder microstructure and mechanical properties from the previous studies. DSC was used to determine the effect of melting characteristics of SAC105 with addition of minor Al or Zn solder. XRD, FESEM, EPMA were used to evaluate the IMC phases and concentration of minor alloying element prior to the shear test and nanoindentation test. Nanoindentation was used to evaluate the mechanical properties of bulk and IMC formed in the solder. Minor addition of Al up to 0.5% promoted formation of small, equiaxed Cu3Al intermetallic particle in the bulk microstructure, which exhibited much higher hardness and modulus as compared to Cu6Sn5 and β-Sn. On the other hand, minor addition of Zn up to 0.5 % did not lead to the formation Cu-Zn compound, but Zn dissolved in Cu-Sn IMC and formed Cu6(Sn,Zn)5. It was found that Zn tends to accumulate at the edge of solder/MC and especially at the IMC/ Cu interface. Results show that the minor addition of Al and Zn does not alter the morphology of the interfacial intermetallic compounds, but they substantially suppress the growth of the interfacial IMC during reflow and after aging. It is suggested that both Al and Zn exert their influence with different mechanism. Al exerts its influence by lowering the activity of reacting species by its presence at the solder/IMC interface. It was suggested Zn exerts its influence the synergy effect of stabilizing Cu6(Sn,Zn)5 and hindering the flow of reacting species at the solder/IMC and IMC/Cu interface. Nanoindentation results showed that with the addition of Zn, the hardness value Cu6(Sn,Zn)5 of has increased and creep performance of SAC+ Zn in the bulk has improved in comparison to SAC105. Shear strengths for samples with addition of Al and Zn have decreased in comparison to SAC 105 after reflow. Failure mode and mechanisms of SAC 105 and SAC + X (X= Al or Zn) are discussed and compared.